The efficacy of early office hysteroscopy in preventing intrauterine adhesions after abortion: a randomized controlled trial - Ni-Chin Tsai; Yu-Yang Hsiao; Yu-Ting Su; Yu-Ju Lin; Fu-Tsai Kung; Ping-Ho Chen; Kuo-Chung Lan (BMC, 2024)
Abstract Background Intrauterine adhesions (IUA) are a challenging clinical problem in reproductive infertility. The most common causes are intrauterine surgery and abortions. We aimed to investigate whether early second-look office hysteroscopy can prevent IUA. Methods A single-center, prospective, two-armed, randomized controlled trial was designed to explore the efficacy of early office hysteroscopy after first-trimester induced abortion (suction dilatation and curettage [D&C]) and to further analyze fertility outcomes. Women aged 20-45 years undergoing suction D&C and desiring to conceive were recruited. Between October 2019 and September 2022, 66 women were enrolled, of whom 33 were allocated to group A (early hysteroscopy intervention). The women in intervention group A were planned to receive 2 times of hysteroscopies (early and late). In group B, women only underwent late (6 months post suction D&C) hysteroscopy. Results The primary outcome was the IUA rate assessed using office hysteroscopy 6 months after artificial abortion. Secondary outcomes included menstrual amount/durations and fertility outcomes. In intervention group A, 31 women underwent the first hysteroscopy examination, and 15 completed the second. In group B (late hysteroscopy intervention, 33 patients), 16 completed the hysteroscopic exam 6 months after an artificial abortion. Twenty-one women did not receive late hysteroscopy due to pregnancy. The IUA rate was 16.1% (5/31) at the first hysteroscopy in group A, and no IUA was detected during late hysteroscopy. Neither group showed statistically significant differences in the follow-up pregnancy and live birth rates. Conclusions Early hysteroscopy following suction D&C can detect intrauterine lesions. IUA detected early by hysteroscopy can disappear on late examination and become insignificant for future pregnancies. Notably, the pregnancy outcomes showed a favorable trend in the early hysteroscopy group, but there were no statistically significant differences. Trial registration ClinicalTrials.gov , ID: NCT04166500. Registered on 2019-11-10. https://clinicaltrials.gov/ct2/show/NCT04166500 .